Physical Activity and Life Satisfaction: An Empirical Study in a Population of Senior Citizens - Wöbbeking Sánchez, Marina; Sánchez Cabaco, Antonio; Bonete-López, Beatriz; Urchaga Litago, José David; Loureiro, Manuel Joaquím; Mejía, Manuel (Frontiers in Psychology, 2021)
Objective: The specialised literature indicates that the two key aspects in active ageing are performing physical activity and life satisfaction. Regarding physical activity, this not only improves physical aspects of senior citizens, but also has a positive impact on mental well-being and satisfaction with one’s own life. The aim is to demonstrate the relationship between these two variables to explain healthy ageing. Method: In a sample of 300 senior citizen subjects, the influence of various sociodemographic variables (age, sex, institutionalisation, and level of education) on the performance of physical activity and life satisfaction, is analysed. The research design is a non-experimental study with two unique cross-sectional and correlational measurement groups. Results: An analysis of the results indicates that people with a higher level of education present differences in physical and motivational reserves. Furthermore, age and institutionalisation have an impact on physical reserves. Analysis using structural equation models allows key relationships between the variables analysed to be predicted, which can guide the implementation of active ageing. Conclusion: Motivational reserves affect healthy cognitive ageing through their positive impact on cognitive and physical reserves.